The didactic of oral communication in Spanish classroom in Senegal: assessment and empowering perspectives in high school le (Ogigia. Revista Electrónica de Estudios Hispánicos, 2016)
In Senegal, the programs and methods implemented in Spanish teaching and learning process preview the construction of oral communicative competence. But in practice this subject only appears like a dialog between teachers and students and text memorization or recitation. Therefore this work proposes theories, activities and strategies based on the Communicative Approach and the Common European Framework for languages so as to empower oral teaching and learning device.
Keywords: didactics; oral communication; spanish as foreign language; senegalese education